MODERN APPROACHES TO THE TREATMENT OF PREMENSTRUAL SYNDROME (World Bulletin of Public Health, 2026)
PMS symptoms can occur at various ages, from the onset of menarche to the onset of menopause. During puberty, the prevalence of PMS ranges from 20% to 80.4%. Mild PMS is optimally managed with non-drug approaches, including exercise, lifestyle modification, and proper nutrition. Patients with moderate to severe PMS with predominantly neuropsychiatric symptoms should be monitored in collaboration with related specialists; it is important to differentiate the syndrome from mental illness and extragenital pathology. Despite the availability of numerous different methods and pharmacological agents for the treatment of PMS, choosing the most optimal treatment strategy is fraught with certain difficulties. Many treatment methods do not eliminate the risk of patients "not responding" to therapy, necessitating further study of the disease's pathogenesis and the development of preventive measures based on modern medical advances.